Performance of monetary policy with internal central bank forecasting - Seppo Honkapohja; Kaushik Mitra (European Central Bank (ECB), 2002)
Recent models of monetary policy have analyzed the desirability of different optimal and ad hoc interest rules under the restrictive assumption that forecasts of the private sector and the central bank are homogenous. In this paper, we study the implications of heterogeneity in forecasts of the central bank and private agents for the performance of interest rules from the learning viewpoint.
Keywords: E52; E31; D84; 330; Adaptive learning; heterogeneity; monetary policy; stability